1999
DOI: 10.1007/s002709900378
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial aneurysms mimicking aortic aneurysms: Endovascular treatment in two patients

Abstract: Bronchial artery dilatation and aneurysm formation is a potential complication of local inflammation, especially in bronchiectasis. When the bronchial artery has an ectopic origin from the inferior segment of the aortic arch, aneurysms may mimick aortic aneurysms. Despite this particular location, endovascular treatment is possible. We report two such aneurysms that were successfully embolized with steel coils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Vernhet et al reported the use of detachable steel coils during endovascular treatment of mediastinal bronchial artery aneurysms of bronchial arteries with ectopic origin [11]. Such aneurysms may mimic as aortic aneurysms because of their proximity to the aorta [11]. We report the use of 3D and 2D detachable coils for treating mediastinal bronchial artery aneurysm in our second case.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Vernhet et al reported the use of detachable steel coils during endovascular treatment of mediastinal bronchial artery aneurysms of bronchial arteries with ectopic origin [11]. Such aneurysms may mimic as aortic aneurysms because of their proximity to the aorta [11]. We report the use of 3D and 2D detachable coils for treating mediastinal bronchial artery aneurysm in our second case.…”
Section: Discussionmentioning
confidence: 85%
“…However, because of advances in the endovascular techniques, exclusion of a bronchial artery aneurysm can be performed by using a stent‐graft [10]. Vernhet et al reported the use of detachable steel coils during endovascular treatment of mediastinal bronchial artery aneurysms of bronchial arteries with ectopic origin [11]. Such aneurysms may mimic as aortic aneurysms because of their proximity to the aorta [11].…”
Section: Discussionmentioning
confidence: 99%
“…Embolization offers an attractive, minimally invasive approach that can be performed in emergent settings (1). Recognizing variations in bronchial arterial anatomy is critical under any circumstances and, in this regard, it was intriguing that, as in our case, an origin arose from the underside of the arch (5,11). Although most reports describe the use of coils, biological glue has also been successfully used (6).…”
Section: Discussionmentioning
confidence: 96%
“…Ligation of the artery could also presumably be considered in patients where the aneurysm is accessible by thoracotomy, and where less invasive methods have failed and/or there are other indications for thoracotomy. Endovascular stent grafts of the thoracic aorta, with or without concomitant embolization, have also been described, particularly in cases where the bronchial artery arises from the underside of the distal arch (5,10). This approach may be needed because it may not be possible to cannulate the vessel and, in the distal arch, it may be possible to avoid completely crossing the origin of the left subclavian artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation